2018
DOI: 10.1136/bjophthalmol-2018-312729
|View full text |Cite
|
Sign up to set email alerts
|

Mild form of oculocutaneous albinism type 1: phenotypic analysis of compound heterozygous patients with the R402Q variant of the TYR gene

Abstract: To cite this version:Solène Monfermé. A mild form of oculocutaneous albinism type 1: phenotypic analysis of compound heterozygous patients with the R402Q variant of the TYR gene. Human health and pathology. 2017. dumas-01787599 Année 2017 Thèse N° 3074 U.F.R. des Sciences Médicales THÈSE Pour l'obtention du DIPLOME D'ETAT DE DOCTEUR EN MEDECINE Discipline : Ophtalmologie Présentée et soutenue publiquement le 07 juillet 2017 par Solène MONFERMÉ née le 5 aout 1988 à Neuilly-sur-Seine A notre respectée coordinatr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
28
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 34 publications
(9 reference statements)
1
28
0
1
Order By: Relevance
“…In this study, we intentionally selected subjects with albinism to represent a diverse sampling of albinism subtypes (see Table 1 ) in order to enhance the probability of observing variation in the central organization of visual pathways. Interestingly we saw disrupted central organization even in subjects with the recently described “tri-allelic” form of albinism ( Grønskov, Jespersgaard, Bruun, Harris, Brondum-Nielsen, Andresen, & Rosenberg, 2019 ; Monferme, Lasseaux, Duncombe-Poulet, Hamel, Defoort-Dhellemmes, Drumare, Zanlonghi, Dollfus, Perdomo, Bonneau, Korobelnik, Plaisant, Michaud, Pennamen, Rooryck-Thambo, Morice-Picard, Paya, & Arveiler, 2019 ; Norman, O'Gorman, Gibson, Pengelly, Baralle, Ratnayaka, Griffiths, Rose-Zerilli, Ranger, Bunyan, Lee, Page, Newall, Shawkat, Mattocks, Ward, Ennis, & Self, 2017 ). Although our sample is not nearly large enough to draw strong correlations among genetic, retinal, and central factors, we did observe variation across our albinism sample in the extent of hemifield overlap, pRF size, incidence of dual pRFs, and the distribution of dual pRFs across the visual field.…”
Section: Discussionmentioning
confidence: 58%
“…In this study, we intentionally selected subjects with albinism to represent a diverse sampling of albinism subtypes (see Table 1 ) in order to enhance the probability of observing variation in the central organization of visual pathways. Interestingly we saw disrupted central organization even in subjects with the recently described “tri-allelic” form of albinism ( Grønskov, Jespersgaard, Bruun, Harris, Brondum-Nielsen, Andresen, & Rosenberg, 2019 ; Monferme, Lasseaux, Duncombe-Poulet, Hamel, Defoort-Dhellemmes, Drumare, Zanlonghi, Dollfus, Perdomo, Bonneau, Korobelnik, Plaisant, Michaud, Pennamen, Rooryck-Thambo, Morice-Picard, Paya, & Arveiler, 2019 ; Norman, O'Gorman, Gibson, Pengelly, Baralle, Ratnayaka, Griffiths, Rose-Zerilli, Ranger, Bunyan, Lee, Page, Newall, Shawkat, Mattocks, Ward, Ennis, & Self, 2017 ). Although our sample is not nearly large enough to draw strong correlations among genetic, retinal, and central factors, we did observe variation across our albinism sample in the extent of hemifield overlap, pRF size, incidence of dual pRFs, and the distribution of dual pRFs across the visual field.…”
Section: Discussionmentioning
confidence: 58%
“…OCA1 individuals often have no pigmentation at all, in the skin, hair, and eyes, but the variety of presentations is a continuous line from no signs of melanin to an almost normal pigmented phenotype, particularly associated with some TYR variants (e.g., R402Q) known to be thermosensitive, and whose pathogenicity has remained controversial for years (Lasseaux et al., 2018; Monfermé et al., 2019).…”
Section: Oculocutaneous Albinism Typementioning
confidence: 99%
“…Illustratively, variants of the TYR gene responsible for oculocutaneous albinism type 1 (OCA1) can elicit either severe forms with a complete absence of pigmentation or forms with a pigmentation that appears normal, particularly in populations with a light phototype. Among 268 patients diagnosed with OCA1 in our recent study, 122 (45.5%) were compound heterozygotes for a known pathogenic TYR variant and the hypomorphic variant c.1205G>A/p.Arg402Gln (hereafter called R402Q) (Lasseaux et al, 2018 (Monfermé et al, 2019) showed that (i) this variant has a variable expressivity and displays incomplete penetrance; (ii) at the dermatologic level, most patients display a light phototype with residual pigmentation and a tendency to tan with age; the skin and hair can have a normally pigmented aspect; and (iii) at the ophthalmologic level, the classical ocular features of albinism are found, although photophobia and iris transillumination are less frequent, and severity scores are lower for various signs, such as foveal hypoplasia. The decrease of visual acuity is variable, ranging from very moderate to severe.…”
mentioning
confidence: 99%
“…a total lack of pigmentation. A þ nystagmus is described as micro-nystagmus by some authors (Monfermé et al, 2019). A þ foveal hypoplasia corresponds to grade 0 or 1 (almost normal fovea), whereas þþþþ corresponds to grade 4 (total absence of fovea) (Monfermé et al, 2019).…”
mentioning
confidence: 99%
See 1 more Smart Citation